Locke’s Reading of Anton Deusing – An Unrecorded Manuscript Index - Walmsley, J. C. (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2022)
This article presents and transcribes a newly identified John Locke manuscript – an index Locke made of Anton Deusing’s De motu cordis et sanguinis itemque de lacte ac nutrimento foetus in utero, dissertationes (Groningen, 1655). Deusing (1612–1666) was a polymath and medical eclectic with a scholastic predisposition who wrote numerous medical texts in the 1650s and 1660s. Locke owned and read several of these works, taking notes from them, and indexing at least two of them during his medical research at Oxford in the mid-1660s. The recovery of this manuscript further underlines Locke’s own medical eclecticism at this time, highlighting the contrast between his views in this part of his career and the empiricism he later came to evince.